Cercospora leaf spot disease management in sesame (Sesamum indicum L.) with plant extracts - Enikuomehin, O.A. (Journal of Tropical Agriculture, 2006)
The efficacy of aqueous leaf extracts of Aspilia africana, Chromolaena odorata, Musa paradisiaca and Tithonia diversifolia to control Cercospora leaf spot of two sesame cultivars (530-6-1 and Pbtil No.1) was evaluated. Sesame plants were sprayed with 7.5% extracts once every two weeks using a pneumatic hand sprayer, from the third week after planting. Results show that all extracts significantly (p<0.05) reduced the incidence and severity of the disease. In particular, extracts of C. odorata and A. africana substantially reduced the number of infected leaves and number of lesions on foliage, and curtailed disease development, which in turn, protected flowers and capsules from infection. Seeds from the plots sprayed with extracts of A. africana, C. odorata and T. diversifolia also had significantly (p < 0.05) lower fungal infection (range: 4.50 to 8.75%) compared to unsprayed plots (10.25 to 13.5%). Likewise, germination percentage of seeds from the sprayed plants was higher (77.0 to 83.5%) than that of control (64.5 to 73.0%). Overall, leaf extracts of A. africana, C. odorata or T. diversifolia were comparable to Bentex T (20% Benlate+ 20% Thiram) in their effect to suppress Cercospora leaf spot disease in sesame cultivars.